The Contemporary Construction of the Chinese Form of Marxist Literary Criticism - Hu, Yamin (Springer Nature, 2023)
This open access book is the first comprehensive and systematic study of Chinese Marxist literary criticism as an independent theoretical form. It discusses and describes the theoretical features of the Chinese form of Marxist literary criticism by refining and re-interpreting the iconic key concepts of "people," "nation," "politics," "praxis," along with the relationships between literature, technology and capital. Literary criticism and value judgment has also been discussed at length with insightful and valuable views being provided. This book is a brilliant introduction to the topic and ideal academic material for global readers to grasp the essence of Chinese Marxist literary critical thought.